A comprehensive phytochemical, biological, toxicological and molecular docking evaluation of Suaeda fruticosa (L.) Forssk.: An edible halophyte medicinal plant. (August 2021) - Saleem, Hammad; Khurshid, Umair; Sarfraz, Muhammad; Tousif, Muhammad Imran; Alamri, Abdulwahab; Anwar, Sirajudheen; Alamri, Abdulhakeem; Ahmad, Irshad; Abdallah, Hassan H.; Mahomoodally, Fawzi M.; Ahemad, Nafees
Abstract: Suaeda fruticosa is an edible medicinal halophyte known for its traditional uses. In this study, methanol and dichloromethane extracts of S. fruticosa were explored for phytochemical, biological and toxicological parameters. Total phenolic and flavonoid constituents were determined by using standard aluminum chloride and Folin-Ciocalteu methods, and UHPLC-MS analysis of methanol extract was performed for tentative identification of secondary metabolites. Different standard methods like DPPH, ABTS, FRAP, CUPRAC, total antioxidant capacity (TAC), and metal chelation assays were utilized to find out the antioxidant potential of extracts. Enzyme inhibition studies of extracts against acetylcholinesterase, butyrylcholinesterase, tyrosinase, α-amylase and, α-glucosidase enzymes were also studied. Likewise, the cytotoxicity was also assessed against MCF-7, MDA-MB-231, and DU-145 cell lines. The higher phenolic and flavonoids contents were observed in methanol extracts which can be correlated to its higher radical scavenging potential. Similarly, 11 different secondary metabolites were tentatively identified by UHPLC profiling. Both the extract showed significant inhibition against all the enzymes except for α-glucosidase. Moreover, docking studies were also performed against the tested enzymes. In the case of cytotoxicity, both the samples were found moderately toxic against the tested cell lines. This plant can be explored further for its potential therapeutic and edible uses. Highlights: Chemical, biological and in-vitro toxicological properties of Suaeda fruticosa extracts were studied. Methanol extract was found to have higher total bioactive contents and comparatively higher antioxidant potential. UHPLC-MS analysis revealed the tentative presence of important secondary metabolites. The plant was found to present weak to moderate toxicity against the tested cell lines.